Review: Uji Sterilitas dan Regionalisasi Laboratorium Sterilitas Badan POM: Review: Uji Sterilitas dan Regionalisasi Laboratorium Sterilitas Badan POM - Henny Setiawati; Bertha Lolo Lukita (Badan Pengawas Obat dan Makanan, 2021)
Sterile products are preparations that meet the physical, chemical requirements and free from microorganisms, both bacteria and fungi. The sterility test is used as one of the parameters for products released from a manufacturer, even though it is not to guarantee entire of the batch meets the sterile requirements. Sterile preparations are manufactured in a facility that has strict environmental characteristics to minimize the risk of microbial contamination. Sterility testing facilities also requires certain facilities to avoid false-positive results, because sterility testing is only be repeated if there is an error in laboratory testing. Sterility test results that give non-sterile results need to be reviewed whether the results obtained are from the product or due to laboratory errors. Sterility testing facilities require large costs. Expensive testing facilities causes the testing are not conducted by all Provincial Laboratory. The regionalized laboratory at Badan POM is a concept to conduct sterility testing that meets national/international guidelines and reduces large costs. This review is based on a literature study covering sterility testing based on national and international guidelines, sterility testing facilities, limitations of sterility testing and investigation of sterility test failure. Additionally, this review will also describe the concept of regionalization of sterility test laboratories at the Indonesian Food and Drug Authority (Indonesian FDA)